COMPARATIVE EVALUATION OF SPORT-BASED EXERCISE MODALITIES FOR REDUCING ARTERIAL HYPERTENSION: A LITERATURE REVIEW - Sylwia Boczek,; Mikołaj Herba,; Katarzyna Kost,; Wiktoria Smyła-Gruca,; Marcin Gruca, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Hypertension is the principal modifiable risk factor for cardiovascular disease worldwide and the leading preventable cause of mortality. Over the past 30 years prevalence has doubled to ≈1.3 billion people. Each 20-mmHg increase in systolic or 10-mmHg rise in diastolic blood pressure approximately doubles cardiovascular and stroke mortality; even modest BP reductions substantially lower cardiovascular events, reducing premature mortality globally.Aim: The aim of this study was to provide a comprehensive review of different types of physical exercise and to compare their effectiveness in reducing arterial blood pressure.Materials and Methods: Between May-July 2025 we searched PubMed, PMC and Google Scholar (MeSH and free-text). Human studies only; included RCTs, non-randomized, cohort, cross-sectional studies, systematic reviews and meta-analyses. Two reviewers screened; heterogeneity precluded meta-analysis; findings narratively synthesized per PRISMA.Research results: Different exercise modalities-including aerobic, resistance, isometric, interval, and mind-body practices-consistently reduce blood pressure, with magnitude varying by modality, intensity and duration. Evidence suggests a dose-response for aerobic training and robust SBP reductions for isometric protocols, while resistance, interval and mind-body interventions provide moderate benefits. Heterogeneity in study designs, populations and quality limits direct comparisons and highlights the need for standardized, high-quality trials.Conclusions: Various exercise types-including aerobic, resistance, isometric, interval, and mind-body practices-consistently reduce blood pressure. Isometric training strongly lowers systolic BP, aerobic exercise shows dose-response benefits up to 150 min/week, and other modalities offer moderate effects. Regular physical activity is a safe, effective nonpharmacological strategy, supporting integration into comprehensive hypertension management.